The levels of ghrelin, TNF-?, and IL-6 in children with cyanotic and acyanotic congenital heart disease - Yilmaz, Erdal; Ustundag, Bilal; Sen, Yasar; Akarsu, Saadet; Kurt, A. Nese Citak; Dogan, Yasar (Hindawi Ltd, 2007)
Background/ Aim. Ghrelin has effects on nutrient intake and growth. The cause of growth retardation in congenital heart disease is multifactorial. The aim of the present study is to investigate the ghrelin in congenital heart disease and the association of ghrelin with TNF-alpha and IL-6. Materials and methods. We measured serum ghrelin and TNF-alpha, and IL-6 levels using specific immunoassay in 68 patients ( 47 acyanotic, 21 cyanotic with congenital heart disease) and in 25 control subjects. Results. In comparison to controls, serum ghrelin, TNF-alpha levels were significantly higher in acyanotic patients and cyanotic patients with congenital heart disease (P < .0001). In acyanotic and cyanotic patients with congenital heart disease, there was a positive correlation between ghrelin and TNF-alpha (r = .485, P < .05 and r = .573, P < .01, resp.). Conclusion. Serum ghrelin levels are elevated in acyanotic and cyanotic patients with congenital heart disease. Increased ghrelin levels represent malnutrition and growth retardation in these patients. The relation of ghrelin with cytokines may be explained by the possible effect of chronic congestive heart failure and chronic shunt hypoxemia.
Keywords: Tumor-Necrosis-Factor; Growth Failure; Cytokine; Protein